Analytic Teaching in a Gifted Classroom (Analytic Teaching, 1985)
Introduction:  My teaching situation is a peculiar one - five days a week of teaching five different grade levels of academically gifted students from grades Four through Eight.  This past year was my third year of teaching the "Acclaim" program (Accelerated Learning And Individual Motivation) located in Marsh Middle School in Castleberry ISD.  The first two years had been good ones, with progress being shown in students in the areas of logic and creative development, the two main goals for the program.  But even with using Anita Harnedeck's Mind Bender Series, syllogisms, board puzzles, etc., I did not truly feel that my students were gaining a solid grasp of how to approach problems in a logical, systematic reasoning fashion.  Overall, I was aware of gaps in their ability to analyze ideas in depth and to express themselves in a verbal or written manner.  Where to find a plan, though,  that would enhance these abilities and give real direction to their thinking and expressive skills?  That was when I learned of the Analytic Teaching course at TWC and enrolled.  It was the beginning of a year-long adventure that I feel confident will last far into the future for both my students and myself, and which already has irrevocably changed my style of teaching.